(untitled) (MODELING: Jurnal Program Studi PGMI, 2026)
The school library plays an important role in supporting the learning process and fostering students’ reading interest from an early age. This study aims to describe the role of the school library in promoting students’ reading interest at MI As-Shaffah, Bengkulu City. This study employed a qualitative approach with a descriptive research design. The research informants consisted of the principal, librarian, teachers, and students. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the library at MI As-Shaffah functions as a learning resource, a medium for fostering reading habits, and a supporting facility for the implementation of the school’s literacy programs. Several initiatives, including reading activities before lessons, scheduled library visits, and teachers’ motivational encouragement, have contributed to increasing students’ reading interest. However, several challenges remain, including the limited availability of attractive reading materials, inadequate library space, and the low frequency of library visits among some students. To address these challenges, the school has undertaken several efforts, including expanding its book collection, improving the library environment to provide a more comfortable learning atmosphere, and organizing various literacy activities. This study concludes that the school library plays a significant role in fostering students’ reading interest when supported by sustainable literacy programs, adequate facilities, and strong collaboration among the principal, teachers, librarians, and parents.